Representasi Makna pada Film Cinta Pertama, Kedua, dan Ketiga - Indra Wiguna Mahfud; Farida Hariyati; Mustiawan Mustiawan (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
The film "Cinta Pertama, Kedua, dan Ketiga" is an Indonesian romantic drama that explores themes of love, family responsibility, and sacrifice. This study aims to analyze the representation of love in the film using Roland Barthes' semiotic approach. The method applied includes analyzing signs, signifiers, and signifieds from several key scenes to uncover both denotative and connotative meanings. The analysis focuses on scenes of dancing, household duties, the giving of a ring, warm colors, a lonely road, separation, and the giving of a birthday gift. The research findings indicate that dancing symbolizes intimacy and freedom, while household scenes represent the burden of emotional responsibility. The ring signifies commitment and family unity, warm colors reflect harmony but also conceal tension, and the lonely road mirrors emotional isolation. Separation and the birthday gift reveal deep sacrifice and enduring memories. In conclusion, the film portrays love not only as a romantic relationship but also as a journey involving personal sacrifice and family responsibility, aligning with Barthes' views on symbolic meaning in visual narratives.